Connection with the environment (society and companies) – Postgraduate studies - Mendoza, Miguel (Acta Herediana, 2026)
The relationship between universities and their surrounding environment—particularly with the productive sector and civil society—has become a central dimension of contemporary higher education. This paper analyzes the importance of strengthening university engagement with society and companies from the perspective of postgraduate education. First, it examines the conceptual framework of university–industry–society interaction and the so-called “third mission” of universities, highlighting its relevance for innovation, knowledge transfer, and sustainable development. Second, it discusses the Peruvian context, identifying institutional and structural challenges that limit effective collaboration between universities and external actors. Third, the paper presents the experience of Universidad Peruana Cayetano Heredia (UPCH), focusing on institutional initiatives aimed at promoting innovation, social responsibility, and collaboration with public and private organizations. Finally, it proposes strategies and indicators to strengthen engagement from graduate programs, emphasizing co-created academic programs, applied research projects, and partnerships with external stakeholders. The study concludes that consolidating institutional structures, fostering collaborative networks, and promoting inclusive and intercultural communication are essential to enhance the social relevance and impact of universities in Peru.